Causes of the Rise and Flourishing of Civilizations - Habibullah Hazem (Integrated Journal for Research in Arts and Humanities, 2022)
A cursory glance at human history makes it very clear that civilizations are born as human beings, reach maturity and growth, and collapse and die due to more internal causes. The death of civilizations is something that history has talked about a lot and it is called forgotten civilizations. In the science of history and more in the philosophy of history, the issue of how the causes and factors of the emergence, flourishing and destruction of civilizations are mentioned and history analysts study these causes and factors. According to them, the mentioned causes and factors are natural and in the field of events related to natural and human laws. But in intra-religious analysis, looking at causes and factors is done from another angle; The Qur'an, with the aim of guiding human beings, looks at events from an educational point of view. On this basis, each of the events is closely related to the issues of punishment and encouragement of human beings and finds meaning and meaning with monotheism and its belongings. Although it is necessary to look at the events and their causes from the perspective of philosophy of history and natural traditions and laws, but these traditions are closely related to human actions and behavior. In a comprehensive analysis, although earthquakes, floods and other natural disasters are related to natural laws, but human actions are effective in its creation and emergence, and these actions can have a positive and negative impact on natural laws and nature. Hence, human behavior and actions can cause the rise and fall of civilizations in a serious way. In intra-religious analysis, God has a permanent presence as the source of all events, and human behavior causes changes in natural causes and factors. Therefore, the issue of the emergence, flourishing and destruction of civilizations from this perspective needs to be analyzed, which will be addressed in this article.